Lateran IV's Decree on Confession, Gratian's De Penitentia, Confession to One's Sacerdos Proprius A Re-Evaluation of Omnis Utriusque in Its Canonistic Context - Larson, Atria A. (2018)
Omnis utriusque, c.21 of the Fourth Lateran Council (1215), is often mentioned for its command to all Christians to confess annually. Scholars often refer to the decree when discussing late medieval confession; some have searched in vain for precise conciliar precedents; they have not yet situated it in its canonistic context. his essay examines various aspects of the constitution to understand its connections to twelfth-century academic discussions and above all to Gratian's De penitentia. It also examines how canonists over the next decade or more understood the constitution. his study concludes that, for canon law and for the incorporation of new clerical orders, Omnis utriusque was equally, if not more important for what it stipulated about confession to one's sacerdos proprius than for its prescription of annual confession.
Keywords: Canon Law; CONFESSION (Christianity); Fourth Lateran Council; Gratian; Gratian, ca. 12th century; Lateran Council (4th : 1215 : Palazzo Lateranense); Penance; Canon Law; Confession; Penance